Tinjauan Semiotika dan Estetika Poster Film Flow (2024) - Fadhillah Fahriansyah; Onang Murtiyoso (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study aims to uncover the mechanisms of visual communication in non-verbal animated film posters through semiotic and aesthetic analysis. The research object selected is the poster for the film Flow (2024), a unique work characterized by the absence of verbal communication in its narrative, thereby placing the entire burden of message delivery on visual elements. The method employed is descriptive qualitative with a two-stage semiotic significance approach by Roland Barthes, reinforced by theories of color psychology and visual composition. The results indicate that the Flow (2024) poster constructs meanings of resilience and non-human agency through the use of a "demand gaze" on the main character, which necessitates the audience's emotional engagement. Aesthetically, the study finds an affective dialectic between the use of cool tones (Midnight Blue), symbolizing ecological isolation, and golden rim lighting accents as a signifier of hope. The massive use of negative space in the poster successfully creates a "sublime" effect, mythologizing the collapse of the Anthropocene era while glorifying the spirit of interspecies survival. This research concludes that the strength of non-verbal film posters lies in the sharpness of visual sign systems that transcend linguistic boundaries to convey complex symbolic narratives. The practical implications of this study provide guidance for visual communication designers regarding the effectiveness of color contrast and spatial dynamics in building a powerful narrative atmosphere.